The Role of Consumer Attitude and Renewable Energy towards Environmental Friendly Policies in the Intention to Comply With the Paid Plastic Environmental Friendly Policy - Sinaga, Anton Atno Parluhutan; Sitorus, Sunday Ade (International Journal of Energy Economics and Policy, 2023)
The purpose of this study is to determine the effect of consumer attitudes and renewable energy on the intention to comply with the paid plastic environmentally friendly policy in North Sumatra Province through the environmental friendly policy variable made by the Government as a moderator variable.In this study the variables used are exogenous variables, namely consumer attitudes and renewable energy, while the endogenous variables areintention to comply with the paid plastic eco-friendly policy in North Sumatra Provinceand the moderator variable isEnvironmentally friendly policies made by the Government. In this study, the data taken were adult population data in North Sumatra Province in 2020 who used as much as of plastic4,177,004 souls. MThe research method used in this study is a quantitative descriptive research method using data analysis, namely path analysis using PLS 3.0 software.Based on the results of the research analysis, the conclusion of this study is partially that only consumer attitude variables affect the intention to comply with paid plastic environmentally friendly policies in North Sumatra Province and consumer attitudes and renewable energy variables affect environmentally friendly policy variables. Simultaneously, consumer attitudes and renewable energy variables affect the intention to comply with the paid plastic environmentally friendly policy in North Sumatra Province with the environmental friendly policy variable as the moderator variable.Through the results of the research that has been stated above, the adults of North Sumatra will have the intention to obey and obey all environmentally friendly policies that are carried out, such as creating renewable energy, where these policies are very useful so that the people of North Sumatra are protected from the dangers of environmental damage and disasters. nature that will happen if you still use energy from fossils that can pollute the land, sea and air.